Biomass integration for energy recovery and efficient use of resources: Tomsk Region; Energy; Vol. 235 - Fan Yee Van; Romanenko S. V. Sergey Vladimirovich; Gai Limei; Kupressova E. A. Ekaterina Alekseevna; Varbanov P. S. Petar Sabev; Klemes J. J. Jiri Jaromir (2021, 2021)
Title screen